PSYCHE STRUCTURE ANALYSIS OF THE MAIN CHARACTER IN THE MOVIE “SOMETHING THE LORD MADE” BASED ON SIGMUND FREUD THEORY - Yeni Monalisa Gultom; Dwi Astarini (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Psychology takes the important role in literature, because the composition of literary work in its story could not beapart from the psychological aspect. Psyche structure is one of the way to analyze the character. The writers applied personality theory from Sigmund Freud that consists of three structures namely the Id, Ego and Superego, These three parts work together to create a complete personality to analyze the main character in “something the lord made” movie that was released in 2004. This movie tells about first doctor who handle “baby syndrome” case. The aim of the research is to find out the psyche structure of Vivian by using theory of Sigmund Freud. The data was obtained from two sources that are primary data which is taken from the movie script directly and secondary dara which is taken from books and journals that supported this research. It was conduct by using qualitative research. Based on the data analysis, the writers found that there was 11 data which related to psyche structure of Vivian Thomas. The analysis of research result shows that psyche structure is used in Something the Lord Made movie.